Training perceptual-cognitive skills in sports using technology - Fadde, P. J.; Zaichkowsky, L. (Journal of Sport Psychology in Action, 2018)
Ballistically reactive sports performances such as blocking a soccer or hockey shot-on-goal, returning a tennis serve, and hitting a pitched baseball or bowled cricket ball depend upon anticipating an opponent`s action. Sport science researchers have found that expert performers in many sports use superior perceptual-cognitive skills to recognize patterns in opponents` actions, thereby priming rapid response selection and motor execution. Researchers have developed technologies and methods for measuring perceptual-cognitive skills that can also be used to improve these skills. After decades of research, technologies are now appearing as viable training products that coaches and sport psychologists can use with athletes. This article describes technologies such as visual occlusion, virtual reality, and 3D multiple object tracking for training perceptual-cognitive sport skills.